Effect of feeding frequency on the growth, survival and net yield of sea bass (Lates calcarifer Bloch) reared in floating net cages - Mangawil, Melvin Z. (Iloilo College of Fisheries, University of the Philippines in the Visayas, 1990)
The effect of feeding frequency on the growth, feed conversion ratio (FCR), survival rate and 11.3 to 11.8 g was investigated in floating net cages installed in a pond for 152 days. Using Acetes sp. and chopped tilapia fingerlings as feeds, sea bass were fed to satiation at different feeding frequencies, namely : 4, 2, and 1 time(s) per day and once in every 1.25 and 1.5 days. Except survival rate, result showed that feeding frequency affected all parameters of production and size frequency distribution of sea bass. Higher mean and BW and net yield of 127.9 g and 4.4 kg, respectively, were obtained in sea bass fed 2 times per day. However, these were not enhanced (P>0.05) in fish fed once every 1, 1.25 and 1.5 day(s). FCR were 5.8, 4.9, 5.1 and 4.8 in sea bass fed 2 times per day and once in every 1, 1.25 and 1.5 day(s), respectively. These FCR values were not significantly different (P>0.05) but were significantly better (P<0.05) than in fish fed 4 times per day. The lower value of FCR observed in fish fed 2 times daily to once in every 1.5 days can be attributed to the amount of food remaining in the fish stomach after the fish has been fed. Result of the preliminary study showed that after a 25-h period, the food taken in by the fish is completely digested. Although no significant differences exist in the FCR of fish fed from once in every 1.5 days to 2 times daily, the higher mean BW observed in the latter was due to efficient consumption of food which is indicated by lower FCR. The high survival rates (89.2-96.7%) obtained in all treatments indicated that cannibalism due to starvation and size hierarchy in the population was prevented. The results of this study suggested that feeding frequency of 2 times per day is optimum for sea bass cultured in floating net cages. Due to high salinity of the pond water that prevailed during the experiment, the growth of sea bass was retarded compared to results reported from previous related studies on this fish.
Thesis (M. S. Fisheries-Aquaculture) - University of the Philippines in the Visayas, November 1990..
Keywords: Animal feeding; Seabass; Lates calcarifer Bloch; Feeding experiments; Feeds and feeding